Carcinoid Syndrome and Carcinoid Heart Disease as Manifestations of Non-Metastatic Ovarian Neuroendocrine Tumour - Simões-Pereira, Joana (2017)
The carcinoid syndrome is rare but it is associated with carcinoid heart disease in more than a half of the cases. Carcinoid heart disease is typically characterised by morphological and functional modifications of right-sided valves. Its aetiology is probable multifactorial but serotonin appears to play a key role in the development of this valvular disease. Unlike gastrointestinal neuroendocrine tumours, ovarian neuroendocrine tumours can present with carcinoid syndrome and carcinoid heart disease in the absence of liver metastases; such ovarian neuroendocrine tumours are a unique clinical entity. The additional burden of cardiac impairment in these patients represents a significant reduction in survival. Early recognition and surgical valve replacement before advanced heart failure is established may improve the clinical outcome. We report the case of a woman with an ovarian neuroendocrine tumour and highly symptomatic carcinoid heart disease who was submitted to tumour resection followed by valvuloplasty. She demonstrated an outstanding clinical improvement and has remained free of tumour and symptomatology.